Politics and the Application of Law: Crime Construction and Police Power - Hassan, Komysha (2017)
The shooting death of Michael Brown in June of 2014 by police in Ferguson, Missouri triggered massive public protests across the United States, calling attention to a wave of similar incidents thereafter, where unarmed black men have been killed at the hands of officers in a wide range of locales. The recent coverage has revealed the extent and dispersion of aggressive and, in many cases, fatal interactions between law enforcement and the public, particularly minorities. Actions by the Department of Justice and other state and local agencies have consistently focused on individual agencies and/or agents, as the cause of the problem. This research looks at the history of crime control policy and the law enforcement mandate, from the 1960s onward, examining disparities in crime policy and incidence. The findings show that the shift from locale-based to centralized crime control and the manipulation of crime as a political construct has led to a change in law enforcement identity, away from public service. Consequently, the governing politics and organizational culture of law enforcement has institutionalized some of the most reprehensible aspects, systematizing misconduct. The findings suggest that resolving the problem of misconduct in law enforcement requires an identity shift, focusing on structural rather than individual concerns and implementing more robust and comprehensive training parameters